Optimalisasi Peran ASEAN Disability Forum dan Akses Pendidikan bagi Kaum Penyandang Disabilitas - Jafar Fikri Alkadrie; Jeniar Mooy (Universitas Jenderal Ahmad Yani, 2016)
One of the ASEAN Socio Cultural Community's priority sectors in ASEAN Community 2015 is social development and welfare focused on the fulfillment of the rights of vulnerable groups including persons with disabilities. To support this sector, in 2011, the Bali Declaration underlined several aspects that could support the fulfillment of the basic rights of persons with disabilities in Southeast Asia, one of which is the activation of the ADF (ASEAN Disability Forum) as a container that has a role in mainstreaming Disability issues in policy making of ASEAN member countries. In this regard, this article seeks to explain how the conditions of education of persons with disabilities in ASEAN member countries and the role and performance of the ADF and its contribution to persons with disabilities in Southeast Asia. The author also describes how the field conditions, obstacles and barriers and optimization actions that can make this ADF program to be successful and succeeded in accordance with the initial ideals previously intended.